Medicinal plants used by "Passo da Ilha" rural community in the city of Pato Branco, southern Brazil - Marchese,José A. (2009)
The scope of this work was to rescue and document the traditional knowledge regarding the medicinal plants used by Passo da Ilha rural community, in Pato Branco, Paraná State, Southern Brazil (26° 11' S, 52°36' W and 760 m high). Structured interviews were made in field research with 16 informants who had the traditional knowledge about medicinal plants. The research was carried out from October to December 2000. The plants were collected in the field, identified and their vouchers were housed at the Herbarium "Irina Delanova De Gemtchjnicov" (BOTU) of São Paulo State University, in Botucatu. A total of 47 botanical families and 114 species of medicinal plants were identified. These plants ere suitable for ore than 30 different edicinal uses. The residents are mainly of European descent, which justify the presence of many exotic plants. The knowledge on how to use medicinal plants properly is held mainly by the females, and decreases in the newer generations, denoting "cultural erosion" in progress.